Relationship between CD 163 Tumor-Associated Macrophages and Colorectal-Cancer Stem Cell Markers - Rey, Imelda; Putra, Agung; Lindarto, Dharma; Yusuf, Fauzi (Open access Macedonian journal of medical sciences, 2021)
BACKGROUND: Colorectal-cancer stem cells (CR-CSCs) represent a specific subpopulation of colorectal cancer (CRC) cells, which are characterized by the expression of CD133 and CD166. Tumor-associated macrophages (TAMs), found near CSCs may represent polarized macrophages, which are characterized by CD163 expression. In most tumors, TAMs may promote aggressive tumor development, leading to poor prognoses. AIM: The aim of this study was to determine whether any association exists between CD163 expression in TAMs and CD133 and CD166 expression in CR-CSCs. METHODS: This study used a cross-sectional design that was conducted at the General Hospital and affiliates in Medan, from September 2018 to July 2019. CRC tissues were collected from colonoscopy biopsies and surgical resections performed on CRC patients, who fulfilled all necessary inclusion and exclusion criteria and provided informed consent. Subjects were divided into high- and low-CD163-level groups. We analyzed the expression levels of CD163, CD133, and CD166 using immunohistochemical (IHC) assays. RESULTS: A total of 118 CRC patients were enrolled in this study, of whom 58.5% were male. No significant differences in hemoglobin, leukocyte, or platelet levels were observed between high- and low-level CD163 expression. We didn’t find any significant association of CD163 TAM with CRC histological grade and TNM stagings. Significant associations were found between the CD 163 expression level and the CD133 expression level (p < 0.001) and between the CD 163 expression level and the CD166 expression level (p< 0.001). Increased TAM levels of CD163 was associated with 2.770-fold and 2.616-fold increased risks of elevated CD133 and CD166 levels, respectively. CONCLUSION: An association was found between the expression levels of CD163 in TAMs and the expression levels of CD133 and CD166 in CR-CSCs.